IMPLEMENTASI KEBIJAKAN PENURUNAN STUNTING DI KABUPATEN MAJENE PROVINSI SULAWESI BARAT - M. Alif Alwan Sadek; Mutia Rahmah; Muchlis Hamdi (ipdn, 2025)
Stunting remains a critical health issue and a national priority program, particularly in Majene Regency. In response, the Local Government of Majene issued Regional Regulation No. 30 of 2019 aimed at accelerating the reduction of stunting prevalence in the region. However, the policy has yet to achieve its intended goals. This research aims to identify and analyze the supporting and inhibiting factors in the implementation of stunting reduction policies in Majene Regency, West Sulawesi Province, and to formulate strategies to optimize policy implementation. The study employs a qualitative approach, gathering data through interviews, documentation review, and observations. Data analysis involves condensation, presentation, and conclusion drawing/verification. Informants were selected using purposive and snowball sampling techniques. Findings indicate that supportive factors include: 1) Precision of stunting reduction policy instruments, 2) Clarity in policy design encompassing procedures, timing, resources, and adaptation of stunting prevalence reduction targets, 3) Clear institutional design involving executing organizations and inter-organizational coordination, 4) Oversight by supervisory bodies, 5) Availability of necessary resources, and perceived community benefits. Conversely, inhibiting factors include: 1) Challenges in policy instrument implementation, 2) Inadequate community oversight, 3) Insufficient required resources, and 4) Low community involvement. Proposed efforts to optimize stunting reduction policy implementation in Majene include enhancing budget absorption for stunting, implementing iron supplementation as a preventative strategy aimed at improving future generation health, and increasing community participation through regular infant counseling and measurement.